Does Reiki Benefit Mental Health Symptoms Above Placebo? - Zadro, Sonia; Stapleton, Peta (Frontiers in Psychology, 2022)
Background Reiki is an energy healing technique or biofield therapy in which an attuned therapist places their hands on or near the client’s body and sends energy to the client to activate the body’s ability to heal itself and restore balance. It was developed in Japan at the end of the 19th century by Mikao Usui of Kyoto. Given the enormous international socioeconomic burden of mental health, inexpensive, safe, and evidenced-based treatments would be welcomed. Reiki is safe, inexpensive, and preliminary research suggests it may assist in treating a wide variety of illnesses. Given that Reiki is a biofield therapy, growing in use, and not yet accepted by the dominant biomedical paradigm, it is important to establish its effectiveness over placebo. This study aimed to examine Reiki’s effectiveness over placebo in treating symptoms of mental health and to explore parameters for its effectiveness. Method A systematic review of randomized placebo-controlled trials (RPCTs) examining Reiki’s effectiveness in treating symptoms of mental health in adults was conducted through a systematic search of PubMed, PsycINFO, MEDLINE, CINAHL, Web of Science, Scopus, Embase, and ProQuest. Fourteen studies met the inclusion criteria, and risk of bias was assessed using Cochrane’s Revised ROB 2 assessment tool. This was followed by a grading of recommendations, assessment, development and evaluations (GRADE) assessment. Results The evidence to date suggests that Reiki consistently demonstrates a greater therapeutic effect over placebo for some symptoms of mental health. The GRADE level of evidence is high for clinically relevant levels of stress and depression, moderate to high for clinically relevant levels of anxiety, low to moderate for normal levels of stress, and low to moderate for burnout, and low for normal levels of depression and anxiety. Conclusion The results suggest that, Reiki may be more effective in treating some areas of mental health, than placebo, particularly if symptoms are clinically relevant. To date, there are a small number of studies in each area, therefore findings are inconclusive and, more RCTs controlling for placebo in Reiki research are needed. Most included studies were also assessed as having a risk of bias of some concern. Incorporating Reiki as a complementary treatment to mainstream psychotherapy for depression, stress, and anxiety may be appropriate. Systematic Review Registration [https://www.crd.york.ac.uk/], identifier [CRD42020194311].